A study of causal attributions for success and failure in mathematics among Brazilian students - Boruchovitch, Evely (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
As causal attributions for school success and failure are central constructs for achievement motivation, an investigation of causal attributions for success and failure in a mathematics exam was carried out among 110 public school Brazilian students. Participants were from both sexes and low SES, and ranged in age from eight to 16 years old. Subjects were interviewed individually and their causal attributions were assessed through 14 yes or no paired items related to a math exam situation. Data revealed that effort and lack of effort were the most important attributions for success and failure. Significant differences emerged between causal attributions and predictor variables. Findings are discussed in terms of their contribution for understanding the role school context plays in enhancing students’ motivation.